2011
DOI: 10.1097/pcc.0b013e3181fe4085
|View full text |Cite
|
Sign up to set email alerts
|

Children with genetic disorders undergoing open-heart surgery: Are they at increased risk for postoperative complications?*

Abstract: Infants with congenital heart disease and genetic disorders are not at increased risk for postoperative mortality. However, a genetic disorder is a risk factor for reintubation and renal insufficiency, whereas infants with trisomy 21 have a higher risk of chylothorax and sepsis. Intensive care providers need to be aware of these differences in morbidity to improve management decisions and parental counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…All of these findings are important and highlight the fact that 22q11.2DS results in increased morbidity, rather than mortality, in this particular patient population. 8,9, 25 The same may not be true in the more complicated cohort with major aorto-pulmonary collateral arteries requiring staged repairs as suggested by Mahle et al 7 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All of these findings are important and highlight the fact that 22q11.2DS results in increased morbidity, rather than mortality, in this particular patient population. 8,9, 25 The same may not be true in the more complicated cohort with major aorto-pulmonary collateral arteries requiring staged repairs as suggested by Mahle et al 7 …”
Section: Discussionmentioning
confidence: 95%
“…7 In addition, non-cardiac abnormalities and malformation syndromes appear to be independent risk factors for prolonged intubation, re-intubation and longer intensive care duration. 8, 9 Therefore, factors related to genotype influence outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It causes congenital heart disease (CHD), hypocalcaemia, cognitive disabilities and psychiatric disease, among other symptoms 1. Several authors have reported an increase in postoperative mortality in paediatric patients with CHD and 22q11DS compared with patients with non-syndromic CHD;2 3 however, this association appears to be controversial and has not been observed by other authors 4–6. In addition, sudden death in adults with 22q11DS has also been described 7.…”
Section: Introductionmentioning
confidence: 99%
“…The clinicians, by contrast, believed that the trisomy 18 diagnosis could not be separated from decisions about intensive care and surgery, because aneuploidy and growth restriction are known predictors of perioperative morbidity and mortality. 15,16 Some clinicians thought that the infant' s chance of survival was so low that it did not outweigh the potential pain associated with cardiac surgery and multiple intensive care interventions, pain that cannot be perfectly controlled despite the best of intentions. These clinicians also were concerned about the burden of suffering for the infant who would experience cold stress, noise, perturbed sleep-wake cycles, limited holding, and impaired bonding.…”
Section: The Fetal Medicine Team's Responsementioning
confidence: 99%